Implementasi Takaful Sebagai Sistem Asuransi Syariah Dalam Jual Beli Mobil pada PT. Mandiri Utama Finance Syariah di Kabupaten Bone - Wulandari, Wiwi; Hamzah, Akzi; Hasbi, Hartas (Green Publisher Indonesia, 2024)
Takaful, as a form of sharia-based insurance, has an important role in providing protection collectively with the principle of mutual help in accordance with Islamic law. This sharia insurance is free from elements of riba, gharar, and speculation, making it a more suitable option for Muslims compared to conventional insurance. In the context of buying and selling, such as car buying and selling transactions at PT. Mandiri Utama Finance Syariah in Bone Regency, takaful is an important solution to provide protection against various risks that may occur in trading activities. This study will further examine the implementation of takaful in the practice of buying and selling in the Islamic financial sector. This study aims to find out the Implementation of Takaful as a Sharia Insurance System in Buying and Selling Cars at PT. Mandiri Utama Finance Syariah in Bone Regency. The type of research used is a type of qualitative research with an Islamic economic approach supported by the use of observation, interview and documentation methods in collecting the required data. The data sources used are primary data and secondary data. The collected data is then processed with steps, namely data reduction, data presentation, and data verification/conclusion drawn. The results of the study show that the car buying and selling system at PT. Mandiri Utama Finance Syariah Bone is that there are several advantages in buying and selling cars, namely sharia without usury interest, fixed installments until the end of the tenor, no penalties and fines with interest and clear contracts ahead and blessings.